RAPID ATTENUATED TOTAL REFLECTANCE–FOURIER TRANSFORM INFRARED SPECTROSCOPIC QUANTIFICATION OF ATENOLOL IN ITS MICROSPHERES AND TABLETS: A GREEN APPROACH - ANNAPOORANI ARJUNAN; RUBY STANLYRAJ; KUMAR MOHAN (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: A solvent-free direct quantification of atenolol (ATN)-loaded microspheres and its tablets by utilizing attenuated total reflectance (ATR)– Fourier transform infrared (FTIR) spectroscopy was the prime objective of the current research work. Methods: Developing a non-destructive analytical method to quantify the polymer-based analyte is a tremendous task. Since there is a lacuna in the analysis of drugs in the presence of interfering formulation excipients, we proposed an ATR-FTIR spectroscopic method for the qualitative and quantitative estimation of ATN in its polymer-based microsphere formulations. This ATR-FTIR spectroscopic analysis is based on the measurement of the absorption bands and deriving the linearity calibration curve for the effective quantification of ATN in its formulations. Results and Discussion: The prominent absorption was found at 1235 cm⁻1 due to the stretching of the C-O-C aromatic ether linkage moiety of ATN. The linearity of absorbance versus the concentration was found in the range 10–100%w/w with the r2=0.9960. The high percentage of recovery of ATN in microspheres and its marketed tablets (99.76 and 99.66% w/w) demonstrates the compliance of the accuracy study limits as per the International Council for Harmonisation guidelines. Precision study results showed acceptable % relative standard deviation values. The limit of detection and limit of quantification values (0.7 % w/w and 2.0 % w/w, respectively) indicated the high sensitivity of the method. The polymer excipients of the ATN-loaded microsphere and in the commercial tablet preparation did not interfere with the active drug. Conclusion: Thus, the developed ATR-FTIR spectroscopic method is non-destructive, solvent-free, green, inexpensive, accurate, and rapid technique for quantitative determination of ATN in their polymer microspheres and tablet formulations.